Spectrum of sonographic changes in hereditary motor and sensory neuropathy with autosomal dominant and X-linked inheritance - E. S. Naumova; D. S. Druzhinin; S. S. Nikitin; S. A. Kurbatov (Нервно-мышечные болезни, 2016)
Background. In the recent years interest towards nerve sonography has largely increased, specifically in terms of differentiating types of hereditary motor and sensory neuropathy (HMSN). The diagnostic possibilities of high-resolution ultrasound (HRUS) compared to standard neurophysiological tools in the peripheral nerve disorders is still a matter of debate.Objectives. Analysis of quantitative and qualitative ultrasound changes of limb nerves in patients with HMSN type 1 and its comparison with anthropometric and nerve conduction study data.Materials and methods. 44 HMSN patients were analyzed: 16 men, mean age 35,9 ± 6,8 years; 16 (37 %) with autosomal dominant type 1А, 11 (25 %) – with 1В type and 17 (38 %) with Х-linked inheritance. Control group included 44 subjects, 16 male; mean age 35,9 ± 6,8 years. HRUS parameters were analyzed bilaterally on the selected levels: cross-sectional area (CSA), visual cross sectional and longitudinal patterns of the median and ulnar nerves, C5, C6, C7 spinal nerves, tibial, peroneal and sciatic nerves. HRUS parameters were compared to standard anthropometric data, nerve conduction velocity and CMAP amplitude.Results. In all HMSN cases CSA was enlarged compared to healthy controls. Greater changes were found in patients with autosomal dominant inheritance. CSA enlargement in С5, С6, С7 spinal nerves was found in patients with HMSN 1A, С6, С7 – in HMSN 1В, С6 – in HMSN 1X, confirming the necessity to include those nerves in the sonographic protocol in patients with HMSN. Three qualitative cross sectional and longitudinal patterns of the investigated arm nerves were identified, distinct for each of the HMSN type. Absence of significant differences in CSA of the upper limb nerves among analyzed types of HMSN makes it unreliable as the differential parameter, opposite to the defined sonographic patterns. Methodological issues and absence of significant quantitative and qualitative data from the lower limb nerves makes it possible to exclude those from HRUS protocol in HMSN.Conclusions. Nerve sonography of the upper limbs could be a useful additional tool in the differential diagnosis of HMSN type 1 when applying described qualitative HRUS patterns.